E-Modul Interaktif Lectora Inspire dengan Pendekatan Realistik untuk Memfasilitasi Pemahaman Konsep Matematis - Alawiyah Mahfudhah; Dewi Hamidah; Eka Resti Wulan (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2022)
Abstract:Face-to-face and distance learning requires primary content such as e-modules. The purpose of this research is to develop an interactive realistic mathematics e-module that facilitates students' understanding of mathematical concepts for linear equation systems of two variables (LESTV). The platform used is the Lectora Inspire application with the development model adopted being the 4-D. The research instrument used a validation sheet, student response questionnaires, and mathematical concept understanding tests. The results showed that the e-Module was valid and could facilitate students' understanding of mathematical concepts. The percentage of result validation by material experts, media experts, and learning experts are 84%, 83%, and 88%. The average value of the student's conceptual understanding test is 71.5, which is at the level of students' conceptual understanding in the medium category. The percentage of student responses through the questionnaire reached 76.8%, which means that the e-module received a good response from students.Abstrak:Pembelajaran tatap muka dan jarak jauh membutuhkan konten penting seperti e-modul. Penelitian ini bertujuan mengembangkan e-modul matematika realistik interaktif yang memfasilitasi siswa dalam memahami konsep matematika pada Sistem Persamaan Linear Dua Variabel (SPLDV). Platform yang digunakan yaitu Lectora Inspire dengan model pengembangan 4-D. Instrumen penelitian yang digunakan adalah lembar validasi, angket respon siswa, dan tes pemahaman konsep matematis. Hasil penelitian menunjukkan e-Module valid dan dapat memfasilitasi pemahaman konsep matematika siswa. Persentase validasi hasil oleh ahli materi, ahli media, dan ahli pembelajaran berturut-turut adalah 84%, 83%, dan 88%. Nilai rata-rata tes pemahaman konsep siswa adalah 71,5 berada pada tingkat pemahaman konsep siswa kategori sedang. Persentase respon mahasiswa melalui angket mencapai 76,8%, yang berarti e-modul mendapat respon yang baik dari siswa.